Discovery and analysis of a novel type of the serine biosynthetic enzyme phosphoserine phosphatase in Thermus thermophilus. (7th December 2018) - Chiba, Yoko; Yoshida, Ayako; Shimamura, Shigeru; Kameya, Masafumi; Tomita, Takeo; Nishiyama, Makoto; Takai, Ken
Abstract : Studying the diversity of extant metabolisms and enzymes, especially those involved in the biosynthesis of primary metabolites including amino acids, is important to shed light on the evolution of life. Many organisms synthesize serine from phosphoserine via a reaction catalyzed by phosphoserine phosphatase (PSP). Two types of PSP, belonging to distinct protein superfamilies, have been reported. Genomic analyses have revealed that the thermophilic bacterium Thermus thermophilus lacks both homologs while still having the ability to synthesize serine. Here, we purified a protein from T. thermophilus which we biochemically identified as a PSP. A knockout mutant of the responsible gene ( TT_C1695 ) was constructed, which showed serine auxotrophy. These results indicated the involvement of this gene in serine biosynthesis in T. thermophilus . TT_C1695 was originally annotated as a protein with unknown function belonging to the haloacid dehalogenase‐like hydrolase (HAD) superfamily. The HAD superfamily, which comprises phosphatases against a variety of substrates, includes also the classical PSP as a member. However, the amino acid sequence of the TT_C1695 was more similar to phosphatases acting on non‐phosphoserine substrates than classical PSP; therefore, a BLASTP search and phylogenetic analysis failed to predict TT_C1695 as a PSP. Our results strongly suggest that the T. thermophilus PSP and classical PSP evolved specificity for phosphoserine independently. Enzymes: Phosphoserine phosphatase (PSP;EC 3.1.3.3 ); serine hydroxymethyltransferase (EC 2.1.2.1 ); 3‐phosphoglycerate dehydrogenase (EC 1.1.1.95 ); 3‐phosphoserine aminotransferase (EC 2.6.1.52 ). Abstract : The serine biosynthetic pathway for the thermophilic bacterium Thermus thermophilus was previously unknown and phosphoserine phosphatase (PSP), an enzyme necessary for the pathway, had not been identified. Here, we identified a novel PSP in T. thermophilus belonging to the same protein superfamily as classical PSPs. However, these two types of PSP are likely to have independently evolved specificity for phosphoserine.